2014
DOI: 10.1002/ejic.201402886
|View full text |Cite
|
Sign up to set email alerts
|

The First Late‐Transition‐Metal Cyclopentadienyl Chelate Complexes with Silylphosphane or Secondary Phosphane Tethers

Abstract: Keywords: Arene ligands / Phosphane ligands / Transition metals / Chelates / NickelWhile phosphane-tethered cyclopentadienyl complexes with tertiary phosphane moieties have extensively been investigated for many metals, this is not the case for such complexes with a secondary phosphane tether. Only a few representatives of such complexes with early-transition-metals are known. Here, we report the first late-transition-metal cyclopentadienyl chelate complexes with silylphosphane or secondary phosphane tethers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 52 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…The same yield was obtained when the deprotonation of 6 was carried out by methyllithium in hexane at -78°C (6). [14] Scheme 3. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 followed by addition of 1,1'-di(2-bromoethyl)ferrocene in THF.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The same yield was obtained when the deprotonation of 6 was carried out by methyllithium in hexane at -78°C (6). [14] Scheme 3. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 followed by addition of 1,1'-di(2-bromoethyl)ferrocene in THF.…”
Section: Resultssupporting
confidence: 54%
“…In contrast, respective ligands with secondary phosphane moieties offer the additional option of reactions of the P–H groups. In order to gain an access to derivatives with secondary phosphane moieties, we recently showed that the nucleophilic ring opening of spiro[2.4]hepta‐4,6‐diene with lithium tert ‐butylphosphide ( 5 ) gives the respective cyclopentadienylalkylphosphanes in 80% yield . The in situ reaction of the anionic ring opening product with iron(II) chloride afforded the disubstituted ferrocene derivative 6 in 70% yield (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] In some cases, however, the cyclopentadienyl as well as the phosphane moieties have been the subject of variations, for example by replacement of the cyclopentadienyl by an indenyl or fluorenyl system. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Variations at the phosphane part include unsymmetrical substitution patterns such as phenyl/alkyl, [5] alkyl/ silyl, [17] or rare cases of secondary phosphane moieties. [17,18] We have investigated complexes such as 2-5 with cobalt, nickel and iron as the metal centers for a long time (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] Variations at the phosphane part include unsymmetrical substitution patterns such as phenyl/alkyl, [5] alkyl/ silyl, [17] or rare cases of secondary phosphane moieties. [17,18] We have investigated complexes such as 2-5 with cobalt, nickel and iron as the metal centers for a long time (Scheme 2). [4,5,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Here we report some new reactions of cyclopentadienylnickel complexes with a secondary phosphane tether.…”
Section: Introductionmentioning
confidence: 99%